The Production of Ethanol from Sugar Beet Waste by Immobilized Saccharomyces Cerevisiae - Al-Hilo, Jasim; J. Mohammed, Thamir; A. Al-Naime, Rana (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Saccharomyces Cerevisiae cells were immobilized in calcium alginate beads and activated charcoal for use in theproduction of ethanol from batch fermentation of sugar beet waste. Treatment of the waste with NaOH to increase theability of lignocellulose material to hydrolysis by acid (2N H2SO4) to monosaccharide and disaccharide (mainly glucos).The high reducing sugar concentration obtained was equal to 9.2gm/100ml (10Brix) after treatment. Fermentationparameters, are (pH, glucose concentration (2.5-25 gm/100ml), immobilized agent concentration (2.5-25 gm/100ml)were studied to find the optimum physiological condition. And the highest ethanol concentration obtained from thefermentation in the presence of 20%(wt/v) calcium alginate was (9.322%(wt/v)) at 13.75%(wt/v) glucose concentrationand pH 5 .The experimental results were correlated by empirical second order polynomial equation with correlationcoefficient 96.734% and variance 93.574%